COST AND CASH FLOW MANAGEMENT AND ITS EFFECT ON FINANCIAL MANAGEMENT STABILITY IN MANUFACTURING COMPANIES IN INDONESIA - Triana, Leni; Yuliah, Yuliah; Bahits, Abdul (International Journal of Multidisciplinary Research and Literature, 2026)
This study aims to analyse the effect of cost management and cash flow on financial management stability in manufacturing companies in Indonesia. Financial stability is an essential factor in maintaining business sustainability, especially amid economic dynamics and increasingly fierce industrial competition. This study uses a quantitative approach and a survey method to examine manufacturing companies as the research object. Data were collected through structured questionnaires and analysed using inferential statistical techniques to test the partial and simultaneous effects between variables. The results show that cost management has a significant effect on financial management stability, with efficient cost control improving the balance between a company's income and expenditures. In addition, cash flow has also been proven to have a significant effect on financial stability, as it reflects a company's ability to meet short-term obligations and support operational activities. Simultaneously, cost management and cash flow contribute more strongly to financial management stability than either does alone. These findings emphasise the importance of integrating cost-control and cash-management policies to achieve sustainable financial stability.